All aboard!: Involvement of medical and pharmacy trainees in antimicrobial stewardship. (19th December 2018) - Childs-Kean, Lindsey M.; Briggs, Heather L.; Cho, Jonathan C.
Abstract: Antimicrobial stewardship (AS) involves the appropriate selection of antimicrobials. Antimicrobial stewardship programs are mandated in hospitals and are expanding to involve outpatient arenas. Multiple articles have been published describing the need for AS education for medical and pharmacy students, beginning early in the students' career to develop into competent AS practitioners. Additionally, publications have described the role and impact of medical and pharmacy trainees on AS programs. Here, we review the published evidence describing medical and pharmacy trainees' involvement in AS and call for future research in this area.